Vigabatrin in Drug-Resistant Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
A double-blind, placebo-controlled, crossover study of oral Vigabatrin (2-3 g/d) as add-on therapy for 31 patients with drug-resistant seizures is reported from the Neurological Clinic, Univ of Bologna School of Med, Italy.